2023
DOI: 10.3390/ijms24108946
|View full text |Cite
|
Sign up to set email alerts
|

Emission Trade-Off between Isoprene and Other BVOC Components in Pinus massoniana Saplings May Be Regulated by Content of Chlorophylls, Starch and NSCs under Drought Stress

Abstract: The aim of this work was to study the changes in the BVOCs emission rates and physiological mechanistic response of Pinus massoniana saplings in response to drought stress. Drought stress significantly reduced the emission rates of total BVOCs, monoterpenes, and sesquiterpenes, but had no significant effect on the emission rate of isoprene, which slightly increased under drought stress. A significant negative relationship was observed between the emission rates of total BVOCs, monoterpenes, and sesquiterpenes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…Similar correlations were found in studies of diurnal and seasonal monoterpene and isoprene emissions that increased with increasing temperature (Chen et al 2019(Chen et al , 2020. Monoterpene emissions were suggested as a combination of stored and immediately synthesized compounds (Staudt et al 1997), in which emission peaked in warm summer (Peng et al 2011;Bai et al 2017;Huang et al 2023) along with low storage in a specific organ. Another study showed that emissions of diterpenes were detected in different seasons (Chen et al 2019), the seasonal variations of temperature-related emission may be attributed to ecological functions throughout plant development.…”
Section: Climate-chemical Components Associationssupporting
confidence: 60%
See 1 more Smart Citation
“…Similar correlations were found in studies of diurnal and seasonal monoterpene and isoprene emissions that increased with increasing temperature (Chen et al 2019(Chen et al , 2020. Monoterpene emissions were suggested as a combination of stored and immediately synthesized compounds (Staudt et al 1997), in which emission peaked in warm summer (Peng et al 2011;Bai et al 2017;Huang et al 2023) along with low storage in a specific organ. Another study showed that emissions of diterpenes were detected in different seasons (Chen et al 2019), the seasonal variations of temperature-related emission may be attributed to ecological functions throughout plant development.…”
Section: Climate-chemical Components Associationssupporting
confidence: 60%
“…After being synthesized during photosynthesis, monoterpenes were usually stored in specialized storage structures, such as resin canals and secretory cells, and they were partly emitted by leaves to the atmosphere (Niinemets et al 2004;Chen et al 2019). One study in bark of Magnolia officinalis also showed that older trees held higher sesquiterpenes and oxygenated monoterpenes than young trees (Huang et al 2023). Some compounds with increasing trend may hold more storage in special structures accompanied with less emission along with growth stages of Pinus tabuliformis trees.…”
Section: Temporal Change Of Chemical Componentsmentioning
confidence: 99%